Best Practice in Provider/Parent Interaction. (February 2017) - Davies, Betty; Steele, Rose; Krueger, Guenther; Albersheim, Susan; Baird, Jennifer; Bifirie, Michelle; Cadell, Susan; Doane, Gweneth; Garga, Deepshikha; Siden, Harold; Strahlendorf, Caron; Zhao, Yuan
In this 3-year prospective grounded theory study in three pediatric settings, we aimed to develop a conceptualization of best practice health care providers (BPHCPs) in interaction with parents of children with complex, chronic, life-threatening conditions. Analysis of semistructured interviews with 34 parents and 80 health care professionals (HCPs) and 88 observation periods of HCP/parent interactions indicated that BPHCPs shared a broad worldview; values of equity, family-centered care, and integrity; and a commitment to authentic engagement. BPHCPs engaged in direct care activities, in connecting behaviors, and in exquisitely attuning to particularities of the situation in the moment, resulting in positive outcomes for parents and HCPs. By focusing on what HCPs do well, findings showed that not only is it possible for HCPs to practice in this way, but those who do so are also recognized as being the best at what they do. We provide recommendations for practice and initial and ongoing professional education.